2021
DOI: 10.1371/journal.pone.0256746
|View full text |Cite
|
Sign up to set email alerts
|

Metal exposure from additive manufacturing and its effect on the nasal lavage fluid proteome - a pilot study

Abstract: The use of metal additive manufacturing (AM) is steadily increasing and is an emerging concern regarding occupational exposure. In this study, non-invasive sampled nasal lavage fluid (NLF) from the upper airways was collected from metal AM operators at the beginning and end of a workweek during two consecutive years with preventive interventions in the occupational setting in-between (n = 5 year 1, n = 9 year 2). During year one, NLF was also collected from welders (n = 6) from the same company to get a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Our measurements confirm that, even though inhalable dust levels are generally low compared to Swedish OELs, specific work tasks can emit high levels of airborne particles, such as open powder handling or post-processing of builds, risking possible exposure. This is in line with our earlier studies on a single site that had potential exposure, which were reduced after the company introduced several preventive actions ( 5 , 32 , 36 ). Expanding our investigations by increasing the number of companies and AM processes, we confirm that the chosen methodology can be successfully applied in the AM setting.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our measurements confirm that, even though inhalable dust levels are generally low compared to Swedish OELs, specific work tasks can emit high levels of airborne particles, such as open powder handling or post-processing of builds, risking possible exposure. This is in line with our earlier studies on a single site that had potential exposure, which were reduced after the company introduced several preventive actions ( 5 , 32 , 36 ). Expanding our investigations by increasing the number of companies and AM processes, we confirm that the chosen methodology can be successfully applied in the AM setting.…”
Section: Discussionsupporting
confidence: 91%
“…We have earlier shown that virgin metal AM powder, when used in powder bed fusion laser beam (PBF-LB) machinery, changes to include a large bulk of smaller particles that may constitute different risks to the AM machine user (AMMU) ( 4 ). Furthermore, we have thoroughly investigated AMMU at a specific site with serial production of AM components, examining their exposure, biological markers, and effects in the nasal mucosa ( 5 , 32 , 36 ). However, these earlier studies were limited to a single AM technique, two different AM powders, and a smaller number of AMMUs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Northern European studies, with results similar to ours in terms of concentration and size of metal NP, demonstrated skin and systemic exposure (detected in urine) in a AM facility workers, and consequent alterations in indicators of inflammation and liver function, with normalization after exposure prevention interventions (Ljunggren et al, 2019(Ljunggren et al, , 2021Assenhöj et al, 2021), stressing once again the need for adequate methods of assessment and control of exposure.…”
Section: Discussionsupporting
confidence: 83%
“…It has been also detected in extracellular matrix of Wharton’s jelly [ 144 ], amnion fluid [ 145 ], pancreatic juice [ 107 , 146 ], urine [ 147 , 148 ] and tears [ 149 ]. Recent results have shown that S100A6 is present in nasal lavage fluid [ 150 ], and its level is elevated in the nasal swabs of COVID-19 patients [ 151 ]. The role of extracellular S100A6 has not been extensively studied.…”
Section: Extracellular S100a6—a Marker Of Pathological Statesmentioning
confidence: 99%